2013
DOI: 10.1371/journal.pone.0081598
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Human Disturbance Can Lead to Local Extinction of Alpine Rock Ptarmigan: New Insight from the Western Italian Alps

Abstract: Alpine grouses are particularly vulnerable to climate change due to their adaptation to extreme conditions and to their relict distributions in the Alps where global warming has been particularly marked in the last half century. Grouses are also currently threatened by habitat modification and human disturbance, and an assessment of the impact of multiple stressors is needed to predict the fate of Alpine populations of these birds in the next decades. We estimated the effect of climate change and human disturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 41 publications
1
67
0
4
Order By: Relevance
“…At all sites, reproductive success was much lower when the snowmelt date was later and the rainfall after hatching was high. The negative effect of a late snowmelt on the reproductive success of the Rock Ptarmigan has been previously reported for the Canigou Massif (Novoa et al 2008), and more recently Imperio et al (2013) found that the early appearance of snow-free ground the previous spring had a favourable effect on Rock Ptarmigan numbers the following year, probably because of higher reproductive success. The fact that our study was carried out at three different sites both in the Alps and the Pyrenees gives stronger support to the relationship between breeding success, snowmelt date and rainfall after hatching.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…At all sites, reproductive success was much lower when the snowmelt date was later and the rainfall after hatching was high. The negative effect of a late snowmelt on the reproductive success of the Rock Ptarmigan has been previously reported for the Canigou Massif (Novoa et al 2008), and more recently Imperio et al (2013) found that the early appearance of snow-free ground the previous spring had a favourable effect on Rock Ptarmigan numbers the following year, probably because of higher reproductive success. The fact that our study was carried out at three different sites both in the Alps and the Pyrenees gives stronger support to the relationship between breeding success, snowmelt date and rainfall after hatching.…”
Section: Discussionsupporting
confidence: 60%
“…Like other cold-adapted species, the Rock Ptarmigan is regularly cited as a potential sentinel species for indicating the effects of climate change, especially in its southernmost habitats (Revermann et al 2012;Imperio et al 2013). Negative trends in Rock Ptarmigan numbers have been recently attributed to climate change both in the Swiss (Revermann et al 2012) and Italian (Imperio et al 2013) Alps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prediction of a shrinking area for the Alpine Rock Ptarmigan with climate warming derives mainly from the paramount importance of the mean July temperature and other variables related to low temperatures (e.g., typical snow-bed vegetation) when modeling the distribution at the mesoscale and macroscale (Revermann et al 2012;Imperio et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many other environmental changes are occurring. For example, as mangrove acreage declines with sea-level rise, changes in colour frequencies can be expected in Bornean gliding lizards Draco cornutus that match the colours of freshly fallen leaves in either mangroves or rainforest [85]; and as snow cover declines with global warming, populations of Alpine rock ptarmigan Lagopus muta and snowshoe hares Lepus americanus will dwindle [86,87]. In aquatic environments, where particulate matter in water absorbs short wavelengths causing a shift towards orange and red, similar evolutionary colour changes can be expected.…”
Section: (D) Wildlife Management and Conservationmentioning
confidence: 99%